Family Coping Mechanism Reviewed From Family Readiness In Children With Chronic Disease - Saputro, Heri; Haida, Ana Ifa Nurul; Yalestyarini, Eva Agustina; Wardani, Lingga Kusuma (Universitas STRADA Indonesia, 2020)
Chronic illness in children has an impact on families such as social, economic, and psychological impacts. This impact can lead to negative emotions such as sadness, stress and even depression. Family readiness is the ability of the family both physically and mentally in the face of something that happens to family members. The purpose of this study to know the relation of family coping mechanism in terms of family readiness in children with chronic diseases in the Nusa Indah Room of Hospital Level II dr. Soepraoen of Malang. The research design uses correlational analytics with cross sectional approach. The population is the whole family of children with chronic disease in Nusa Indah Room, Hospital dr. Soepraoen of Malang with sample amounted to 44 respondents and taken by purposive sampling. Data collection using questioner then analyzed by chi square test. The result showed that family readness in children with chronic disease mostly (70,5%) ready, family coping mechanism mostly (61,4%) adaptive category. The result of the analysis showed that there was a significant correlation between family readness with family coping mechanism in children with chronic disease with p (sig.) 0,000<0,05. The more ready family then the more positive (adaptive) coping mechanisms that are formed by families in children with chronic diseases. Family readiness is a very important aspect to support the formation of adaptive coping mechanisms in families with children suffering from chronic diseases